A new simpler way to obtain high fusion power gain in tandem mirrors. (24th March 2017) - Fowler, T.K.; Moir, R.W.; Simonen, T.C.
Abstract: From the earliest days of fusion research, Richard F. Post and other advocates of magnetic mirror confinement recognized that mirrors favor high ion temperatures where nuclear reaction rates 〈 σ v 〉 begin to peak for all fusion fuels. In this paper we review why high ion temperatures are favored, using Post's axisymmetric Kinetically Stabilized Tandem Mirror as the example; and we offer a new idea that appears to greatly improve reactor prospects at high ion temperatures. The idea is, first, to take advantage of recent advances in superconducting magnet technology to minimize the size and cost of End Plugs; and secondly, to utilize parallel advances in gyrotrons that would enable intense electron cyclotron heating (ECH) in these high field End Plugs. The yin-yang magnets and thermal barriers that complicated earlier tandem mirror designs are not required. We find that, concerning end losses, intense ECH in symmetric End Plugs could increase the fusion power gain Q, for both DT and Catalyzed DD fuel cycles, to levels competitive with steady-state tokamaks burning DT fuel. Radial losses remain an issue that will ultimately determine reactor viability.